Pengaruh Pemberian Jus Buah Pepaya (Carica papaya L.) terhadap Penurunan Kadar Malondialdehid dan Asam Urat - Janette Rindana Paranoan; Harra Ismi Farah; Adam M. Ramadhan (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Malondialdehyde (MDA) is a biomarker of oxidative stress due to the presence of free radicals in the body. Papaya fruit contains vitamin C and ?-carotene which are useful as antioxidants. This study aims to determine the initial description of MDA levels in urine and uric acid in smoker and non-smoker respondents and to determine changes in urinary MDA and uric acid levels after administration of papaya fruit juice (Carica papaya L). The research method used was experimental with a pre-post test design. The results obtained at the initial MDA level of urine of smokers and non-smokers were an average of 2.504 nmol / mL and 1.821 nmol / mL and the results obtained after giving the juice on day 7 were 1.455 nmol / mL and 0.992 nmol / mL . Meanwhile, the initial uric acid levels of each respondent were 9.6 mg / dL and 8.4 mg / dL and the results obtained after giving the juice on day 7 were 7.8 mg / dL and 6.8 mg / dL. . So it can be concluded that the provision of papaya fruit juice can reduce the levels of MDA in urine and uric acid.